Preventive intraoperative methods for restoring urine function after laparoscopic and open radical prostatectomy - A. A. Lyulko; A. A. Burnaz; I. N. Nikityuk; A. S. Sagan; M. V. Varvashenya (Сучасні медичні технології, 2021)
Purpose of the study. To evaluate the effectiveness of preserving the anatomical structures surrounding the prostate gland for prophylactic intraoperative restoration of urinary retention functions in the postoperative period.